Literature Review Pengaruh Komunikasi antara Orang Tua dan Remaja tentang Kesehatan Reproduksi terhadap Perilaku Seksual Remaja: Literature Review Pengaruh Komunikasi antara Orang Tua dan Remaja tentang Kesehatan Reproduksi terhadap Perilaku Seksual Remaja - Vira Sartika Devi; Era Nurisa; Miftahul Jannah; Rismaina Putri (Universitas Islam Jember, 2021)
The high rate of adolescent mortality due to reproductive problems such as HIV and AIDS is due to the lack of access to adolescent reproductive health services. Many adolescents under the age of 20 have had sexual intercourse, which will cause problems for both the mother and the baby during childbirth. To determine the effect of communication between parents and adolescents about reproductive health on adolescent sexual behavior. This study used a literature study from articles or journals spanning the years 2011-2020. The articles were collected from the database of Science Direct, Scholar, Scopus, Elsevier, PubMed, Sage, Researchgate, NCBI, Garuda Dikti Portal. Many factors influence communication between parents and adolescents, which are internal factors such as parental status, restrictions on male parents, how long they have lived together, education level, knowledge, and age of adolescents and parents, number of families, perceptions, comfort level, motivation, sexual experience, and religion. External factors such as economic status, providing communication in early adolescence and at high risk, only on the same sex, focus on women, peers, culture, and race/ethnicity. Parents and adolescents in all journals have communicated about sexual and reproductive health. Adolescents who have communicated with their parents are those who are sexually active and the lack of communication with their parents makes them look for information on their own that can increase risky sexual behavior. Keywords: Communication, reproductive health, sexual behavior